The administrative employees' perception towards corporate social responsibility and job satisfaction in UiTM Cawangan Pahang Jengka / Nurfazeela Ismail campus - Ismail, Nurfazeela (Faculty of Business and Management, 2018)
The research alms to study the Relationship between Administrative Employees' Perceptions towards CSR and Job Satisfaction in Universiti Teknologi Cawangan Pahang, Jengka Campus. The limitation of this study was focused on the employees in UiTM Cawangan Pahang, Jengka Campus. This research was focused on the components of corporate social responsibility and the level of job satisfaction among the employees. Regarding the Krejcie and Morgan table (1970), the scope focused on 100 number of population. The sample size for this research is 80 people are referred size for 100 populations. The questionnaire was distributed to 80 respondents in UiTM Cawangan Pahang, Jengka Campus. There are seven component of corporate social responsibility consist of economic responsibility, legal responsibility, ethical responsibility, philanthropic responsibility, charity principle, stewardship principle and environmental friendliness